Immunological impact of taekwondo competitions - Lee, Y. W.; Shin, K. W.; Paik, I.-Y; Jung, W. M.; Cho, S. Y.; Choi, S. T.; Kim, H. D.; Kim, J. Y. (International Journal of Sports Medicine, 2012)
Immunological changes in elite adolescent female athletes during Taekwondo competitions were investigated on-field. 6 female athletes (16.7±0.8 year-old) volunteered and performed 5 bouts of demonstration Taekwondo competitions simulating real tournaments in intensity, duration, and break-time intervals on the same day. Blood samples were taken before, after the competitions and during the recovery, respectively. Immunological changes and oxidative stress in peripheral blood mononuclear cells were evaluated by flow-cytometry. During the competitions, exercise intensity was 92.2±3.8% (86.1~95.7) of the maximal heart rate. Blood lactate increased immediately after the competitions (p=0.0165) and decreased to baseline during recovery. Intracellular reactive oxygen species (ROS) in the peripheral blood increased continuously during recovery (p<0.05, respectively). Natural killer cells increased immediately after the competitions (p=0.0006), and decreased during recovery. B and T cells increased immediately after the competitions and remained elevated throughout recovery (p<0.05, respectively). CD4/CD8 ratio after the competitions was decreased (p=0.0091) and returned to baseline during recovery. These results suggest that the immunological function of the elite female adolescent athletes could be attenuated after Taekwondo competitions. Further large-scaled Taekwondo studies on immunologic and apoptotic changes related to oxidative stress should be performed for improving and protecting the health of adolescent athletes.